Bioethical And Legal Considerations Of Genetic Information And Prenatal Diagnosis - Rodríguez-Cadilla Ponce, María Del Rosario (2015)
The objective of the research is to analyze the most important bioethical issues in prenatal diagnosis and to highlight that although these studies permit early diagnosis of abnormalities which could be used to take preventive measures, even operations that could heal them, it also gives the opportunity to examine the possibility of interrupting the pregnancy if the fetus presents conditions that are incompatible with life. While it is true that not all countries allow eugenic abortion, this does not mean that it does not carry many ethical dilemmas. On one hand we have the protection of personal liberties, and on the other the social responsibility involved. This is why we approach this issue from the point of view of Bioethics and Law in order to guide and to reconcile the freedom of research and the respect for the dignity of human life. Our recommendation is to take measures to preserve the confidentiality of such information, and to avoid discrimination among citizens based on the